Paleozoic Episodic Magmatism in Western Tianshan: Insight Into Assembling the Northeastern Pangea - Kai Wang; Keda Cai; Min Sun; Chun‐Kit Lai; Xiao‐Ping Xia; Xiangsong Wang; Zihe Bao (Geochemistry, Geophysics, Geosystems)
Abstract The late‐stage union of Pangea was associated with the convergence of Siberia with Laurussia, but the exact timing remains unclear. The orogenic duration of the Kazakhstan block can provide geochronological constraints as it connects Siberia, Baltica, and Tarim. Zircon petrochronology offers a reliable approach for ascertaining the lifespan of an ancient orogen. In this study, we explore three phases of magmatism recorded in detrital zircons from late Paleozoic and Mesozoic sandstone‐siltstones in Western Tianshan, that is, 400–470 Ma, 320–380 Ma, and 280–320 Ma. Based on their age‐propagated Hf isotopes, melt SiO2 contents, and crustal thicknesses, our findings suggest that the southern limb of Kazakhstan underwent the early Paleozoic amalgamation of microcontinents with arcs, the late Paleozoic maturation of an Andean‐like continental arc, and the late Carboniferous collision of Kazakhstan with the Junggar oceanic basin and the Tarim craton. Such characteristics manifest the long‐term orogenic progression of Kazakhstan. Combining published timelines and paleolatitudes of major orogens and blocks, we propose that the Kazakhstan block welded northeastern Pangea along with the cessation of these orogenic activities around it. Consequently, by docking Kazakhstan with surrounding cratons, the fundamental configuration of Pangea could have been established in the late Carboniferous.